Nilai Pendidikan Karakter dalam Novel Santri Pilihan Bunda Karya Salsyabila Falensia - Ratih Utami Ramadhaniati; Darningwati Darningwati; Triska Purnamalia; Siti Aisyah (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2023)
Analysis of the value of character education in the novel Santri Pilihan Bunda by Salsyabila Falensia can be used in learning literature at school, related to the values ​​in the novel Santri Pilihan Bunda. The purpose of this study was to describe the values ​​of character education in the novel Santri Pilihan Bunda and to describe the values ​​of character education in the novel Santri Pilihan Bunda towards literature learning in high school. The method used in this research is descriptive qualitative method. This study uses two sources of data, namely primary data and secondary data. Data collection techniques use documentation by searching for data in the form of notes, books, ledgers, and so on. This data analysis technique uses several steps, namely classifying character education values, making in-depth descriptions of character education values, interpreting the analysis results, and making conclusions. As for the values ​​of character education contained in the novel Santri Pilihan Bunda, namely religious values, honest values, responsible values, friendly values, and discipline values. It is hoped that this Novel of Santri Pilihan Bunda will add insight to readers and teachers as an additional reference for teaching the value of character education contained in the novel Santri Pilihan Bunda.